Effect of Feeding Different Forms of Zinc on Growth Performance of Male Crossbred Calves - Kachhadia, Laxit; Katole, Shrikant B; Pandya, Paresh R.; Patil, Ghanshyam (Indian Journal of Animal Nutrition, 2023)
The experiment was conducted to determine the effect of replacing inorganic zinc with lower level of organic and nano zinc on feed intake, growth performance, FCR and feeding economics of male growing calves. Fifteen male crossbred calves (93.39±3.19 kg; 8-10 months) were randomly allocated into three groups (n=5). These calves were fed with basal diet consisting of total mixed ration (TMR) having 50:50 roughage to concentrate ratio with 2 kg of green fodder. Along with basal diet experimental groups were provided with additional Zn sources i.e., zinc sulphate (ZnSO4, @40 ppm) in T1, Zn-glycinate (@20 ppm) in T2 and nano ZnO (@10 ppm) in T3 at 50% and 25% level of inorganic Zn supplementation, respectively, for the period of 98 days. All the calves were weighted bi-weekly. Among the groups, dietary Zn supplementation did not affect the feed intake, average daily gain and FCR of the animals significantly (P>0.05). However, numerical improvement in average daily gain and FCR of nano ZnO supplemented groups was observed. Also, cost per kg weight gain was found to be lower in the nano ZnO supplemented group. It may be concluded that, supplementation of nano ZnO (@10 ppm), Zn-glycinate (@20 ppm) and ZnSO4 (@40 ppm) gave comparable (P>0.05) results on growing crossbred calves without any adverse effect.